THE IMPACT OF DIGITAL AND INNOVATIVE TECHNOLOGIES ON ENHANCING STUDENT ENGAGEMENT IN SPORTS ACTIVITIES - Berdiyev Dilmurod Nomonovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the influence of digital and innovative technologies on student engagement in sports activities. The study highlights how technological tools, including mobile applications, wearable devices, and virtual platforms, improve participation, motivation, and performance monitoring. Integrating these technologies into sports education creates interactive and inclusive learning environments, fosters collaboration, and enhances students’ organizational and leadership skills. The article emphasizes the pedagogical advantages of using innovative technologies to increase active involvement and achieve better educational outcomes in sports programs.